Forage and grain sorghum double-cropped following harvest of small grain silages - Gerry L. Posler; K. Bolsen (Kansas Agricultural Experiment Station Research Reports, 1977)
The attempt to increase total forage TDN per acre by double-cropping was only moderately successful in 1975 and 1976. Limiting factors were relatively poor stands and extremely dry summer growing seasons.
Keywords: Report of progress (Kansas State University. Agricultural Experiment Station); 291; Cattlemen' s Day; 1977; Beef; Forage sorghum; Grain sorghum; Yield